GLOKALITAS SAPE"™ SEBAGAI KEARIFAN LOKAL KALIMANTAN BARAT - Olendo, Yudhistira Oscar; Putra, Zakarias Aria Widyatama; Sagala, Mastri Dihita; Syam, Christanto; Ghozali, Imam (Jurnal Kajian Pembelajaran dan Keilmuan, 2023)
Local ethnic culture like sape"™ provides solid local wisdom value for West Kalimantan people. Hence, in the rapid development of smart society 5.0, sape"™ as local wisdom faces stagnant situation as it is urged to view it as culture glocalization. The purpose of this study was to identify sape"™ in the landscape of West Kalimantan"™s local wisdom. In addition, this study aimed to explain sape"™ glocalization from the view of digitalization. This study was conducted through qualitative approach. The method of this study was existential phenomenology. The instrument of this study were unstructured observations and depth interview. The participant were practitioner, artist, and 5 sape"™ musicians. Data analysis technique was conducted through Van Kaam phenomenology: 1) grouping; 2) elimination; 3) thematic portray; 4) validation; 5) textural description; 6) structural description and; 7) textural-structural phenomenon description. This study found that the phenomenon of sape"™ as local ethnic culture had influenced local wisdom to glocalization. This means that sape"™ excitement was created by local cultural performance from the visual landscape of digitalization (glocalization). Sape"™ glocalization as West Kalimantan local wisdom became new concept of Indonesia heritage as it needs to be considered as UNESCO recognition. Moreover, this considers as the future work for researchers, reviewers, and sape"™ musicians to conduct more studies about local culture and global culture.